The Management Of Operational Assistance For Quality Management (OAQM) At SMA Negeri 3 Salatiga In The Academic Year Of 2010 - Qosimiyati, Sri Handayani (2012)
This study aims to describe the characteristic of OAQM fund policy at SMA Negeri 3 Salatiga, and to describe the use of OAQM fund at SMA Negeri 3 Salatiga. This study is a qualitative study using ethnography design. The study is done at SMA Negeri 3 Salatiga. The informant includes the principal and OAQM committee. Data collection method of this research paper uses in-depth interview, observation, and documentation. Data analysis uses an interactive model of analysis started by data reduction, data display, and drawing conclusion. Data validity includes the credibility, transferability, dependability, and confirmability. This study has two findings. The first finding concludes that the OAQM fund policy has four characteristics. The first characteristic is that the policy is started by the formation of OAQM committee which is formed and selected by the school board and the principal based on the principals decree. The structure of the committee in the OAQM management consists of the responsible person, leader, secretary, treasurer, and the responsible person of the program. The second characteristic includes the preparation of OAQM fund submission proposal which is done by the OAQM committee. The third characteristic of OAQM fund policy is that the determination of OAQM program is through SWOT analysis, in which each program has its responsible person and has a role based on their duties. And the last characteristic of OAQM fund policy is that the committee and the principal prepare the budget plan or OAQM. The second finding shows that the use of OAQM fund is relevant to the budget or OAQM programs which have been set. Those programs include the new students' recruitment activity, the daily test or learning evaluation, the remedial activity or students' enrichment, the implementation of learning process, and office supplies. The use of OAQM fund is done by the principles of accountable, transparent, democratic, effective and efficient, orderly administrative and reporting, self-management, participatory and mutual trust. The use of fund for the procurement of goods is accompanied by the administration and special reporting in the form of work order, official report of the procurement and checking of goods. The accountability for the use of fund is done in the form of the preparation of report by the OAQM committee.